Effect of Commonly Used Whitening Toothpastes and Bleaching Agents on the Microhardness of Composite Resins - Aleena Shaheryar Sadiq; Dr.Sarah Shami; Dr Ashar Hussain; Dr Shafquat Hussain Khuwaja; Dr. Umar Farooq Khan; Dr Abdul Qadir (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: The popularity of whitening toothpastes and bleaching agents has increased with rising esthetic demands. Although effective for tooth whitening, these agents may adversely influence the surface properties of restorative materials such as composite resins. Microhardness is a key factor that determines resistance to wear and long-term performance of restorations. Aim: To assess the effect of commonly used whitening toothpastes and bleaching agents on the microhardness of composite resins in a clinical cross-sectional setting. Materials and Methods: This cross-sectional study was conducted over six months.. A total of 100 patients (aged 18–40 years) with existing composite resin restorations were selected using a stratified random sampling technique. Data on the type of whitening toothpaste, exposure time, and bleaching agent usage were collected using a structured questionnaire and clinical examination form. Composite resin restorations from enrolled patients were evaluated using a Vickers microhardness tester under standardized conditions. Collected data were analyzed using SPSS version 26, with ANOVA and chi-square tests applied to determine associations. Results: Patients using whitening toothpastes exhibited a mild but significant reduction in the microhardness of composite restorations compared with those using non-whitening toothpastes. Among whitening agents, abrasive-containing formulations showed greater reduction. In patients who claimed regular bleaching agent containing high concentration hydrogen peroxide, microhardness showed decreased.. Statistically significant (p < 0.05) were the discrepancies across the groups. Conclusion: Both whitening toothpastes and bleaching solutions reduce the microhardness of composite resin restorations; bleaching agents show a greater detrimental effect.Dental professionals should provide thorough guidance to patients with composite restorations who employ these whitening solutions so that they can keep the endurance of their restorations.